Augmented Reality-Based LKPD Innovation Using Assemblr Edu for Atomic Structure Content - Agustina, Shayda; Hasby; Prasetya, Cyndi (Universitas Islam Indonesia, 2026)
Teaching chemistry on the topic of atomic structure still faces challenges due to its abstract nature and the limitations of teaching materials in visualizing the concept. The use of Assemblr Edu, which provides interactive AR-based three-dimensional (3D) visualizations that are easily accessible via mobile devices, offers an alternative solution. However, previous studies generally still use AR as a standalone medium and have not yet integrated it into structured teaching materials such as student worksheets. This study aims to develop and determine the validity and practicality of AR-integrated LKPD based on Assemblr Edu for atomic structure material. This study is a research and development project using the ADDIE model, limited to the development stage. The research subjects consisted of 1 chemistry teacher, 2 expert validators (content and media), and 20 10th-grade students at SMA N 2 Langsa for the 2024/2025 academic year. The instruments included a needs analysis questionnaire, expert validation, practicality assessment, and validated student response data. Data were analyzed using Aiken’s V index and percentages. The results indicate that the worksheets possess high validity with Aiken’s V values of 0.86 and 0.88, as well as practicality rates of 90.6% (teacher) and 84.4% (students), both falling into the “very practical” category. Thus, the AR-integrated LKPD based on Assemblr Edu is suitable and practical for use. The novelty of this study lies in the integration of AR into structured instructional materials. This study is limited to testing validity and practicality; therefore, its effectiveness on learning outcomes has not yet been examined.